Spatial Effects on Rice Exports in ASEAN Countries - Sri Herliana; Dedi Budiman Hakim; Tanti Novianti; Yusman Syaukat (HABITAT, 2023)
Rice trade was also influenced by the proximity factor between regions. This study analyzed the influence of spatial effects on rice exports in ASEAN countries. The analytical method used in this study is a quantitative method and Spatial panel data regression was used in analyzing spatial effects using panel data regression analysis.  The data used was panel data with a time series from 2005 to 2019 and between individuals covering 10 ASEAN member countries, namely the Philippines, Indonesia, Malaysia, Singapore, Thailand, Brunei Darussalam, Vietnam, Cambodia, Laos, and Myanmar. Data processing was assisted by using the R Studio application. Based on the regression analysis of spatial panel data to see the spatial effect on intra-ASEAN rice exports, it can be concluded that there was a spatial effect on intra-ASEAN rice exports. In addition, the results of this study also show that there was a relatively weak spatial agglomeration in rice exports in the ASEAN region.